Cultivation trials of hop (Humulus lupulus L.) in semi-arid environments - Roberto Marceddu; Alessandra Carrubba; Mauro Sarno (Heliyon, 2020)
The recent developments in the market and craft beer industry in Italy have led to an increasing demand for local raw materials, such as barley malt and hops. Few works have been addressed to evaluate suitability and productivity of hop in semi-arid Italian environments. With this purpose, two experiments were carried out in 2018 and 2019, testing the suitability to cultivation of three commonly used hop varieties (Cascade, Chinook and Nuggett) in two typical semi-arid environments in Sicily. Phenological stages were also evaluated, and GDDs accumulated in vegetative and reproductive stages were calculated according to 9 different methods, dealing with three Tbase temperatures (0 °C, 5 °C and 10 °C) and with different adjustments of daily thermal sums for Tmax values >30 °C. The obtained hop cones were used to prepare small batches of beer (fresh hop American Pale Ale), further submitted to sensory analysis through a panel test.The results have shown a high variability of yields and biometrical characteristics of the tested hop varieties according to the cropping management. However, a definite advantage showed up for the earliest maturing variety (Chinook), that allowed cones yield of 41 g per plant (d.m.) and biomass yield of 143 g per plant (d.m.). The sensory analyses assessed the excellent organoleptic characteristics of the obtained hop, as well as of the beer produced. Hop demonstrates to be a promising crop for semi-arid Mediterranean environments, although many aspects of cropping technique are still to be pointed out.